2022
DOI: 10.1038/s41392-021-00762-6
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signalling: function, biological mechanisms, and therapeutic opportunities

Abstract: The Wnt/β-catenin pathway comprises a family of proteins that play critical roles in embryonic development and adult tissue homeostasis. The deregulation of Wnt/β-catenin signalling often leads to various serious diseases, including cancer and non-cancer diseases. Although many articles have reviewed Wnt/β-catenin from various aspects, a systematic review encompassing the origin, composition, function, and clinical trials of the Wnt/β-catenin signalling pathway in tumour and diseases is lacking. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
390
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 784 publications
(572 citation statements)
references
References 340 publications
4
390
0
Order By: Relevance
“…Under physiological circumstances, the binding of Wnt-protein ligand to a membrane receptor initiates an intracellular cascade that disrupts the destruction of the b-catenin complex, consisting of axin, APC, CK1a, and GSK3b [ 87 ]. Consequently, the accumulation of b-catenin into the nucleus, and the interaction with specific transcription factors promote cell proliferation and morphogenesis [ 88 ]. The immunohistochemical distribution pattern of b-catenin was examined in an extensive series of 149 different sellar tumors, including PAs, CPs, arachnoid cysts, RCCs, and XGs [ 89 ].…”
Section: Beyond Imaging Diagnosis: the Molecular Profile Of Sellar Xa...mentioning
confidence: 99%
“…Under physiological circumstances, the binding of Wnt-protein ligand to a membrane receptor initiates an intracellular cascade that disrupts the destruction of the b-catenin complex, consisting of axin, APC, CK1a, and GSK3b [ 87 ]. Consequently, the accumulation of b-catenin into the nucleus, and the interaction with specific transcription factors promote cell proliferation and morphogenesis [ 88 ]. The immunohistochemical distribution pattern of b-catenin was examined in an extensive series of 149 different sellar tumors, including PAs, CPs, arachnoid cysts, RCCs, and XGs [ 89 ].…”
Section: Beyond Imaging Diagnosis: the Molecular Profile Of Sellar Xa...mentioning
confidence: 99%
“…Our study found that SFRP5 was unexpectedly up-regulated (3-folds) in the high-risk group, and the reason may be caused by the epigenetic silencing of SFRP5 in the high-risk group (Su et al, 2010). In addition, as the Wnt pathway plays a pivotal role in organ development (Liu et al, 2022), it is not difficult to explain why lots of the DEGs are associated with organ development in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Activation of the pathway and recruitment of Axin and associated proteins (GSK3β, CK1α, APC) to Fz-LRP5/6 in the membrane negatively regulates the β-catenin destruction complex. β-catenin can then translocate to the nucleus to act as a transcription factor for genes that encode proteins involved in cell proliferation, differentiation, and stem cell maintenance [ 62 ] ( Figure 3 , panel A). In the non-canonical PCP pathway, WNT ligands bind to Fzd receptors and the RAR-related orphan receptor (ROR) and signals to the cytoplasmic phosphoprotein Dishevelled (DVL), which activates Rho-associated (ROCK) or the JUN-N-terminal kinase (JNK), thus inducing gene expression by the activator protein-1 (AP-1) [ 63 ] involved in cytoskeletal rearrangement, cell motility, and coordinated cell polarity ( Figure 3 , panel B).…”
Section: Wnt In Lung Cancermentioning
confidence: 99%